Dissemination of climate information to small-holder farmers: a case study for Mujika area, Zambia - Nanja, Durton Hamooba (University of the Free State, 2010)
Most scientists globally agree that human activities are causing global climate change resulting in pressures on Africa‟s agriculture systems and economies. Knowledge gaps still exist in coping with climate change and adaptation, regardless of the increasing country level research on the agricultural systems. With climatic information dissemination and appropriate policy development as major global themes, literature and knowledge on dissemination of climatic information is still limited in Zambia. This study was undertaken in Mujika area of Monze district, southern province of Zambia from 2007 to 2010. Faced with climate change challenges, the Mujika community opted to investigate the possibility of developing an agrometeorological extension strategy. This strategy was to respond to community needs for routine dissemination of climatic information, serving as a warning as well as guide to improving the local agricultural decision making. This study addressed the following specific objectives: To analyze long-term rainfall data for two stations as a basis for developing climate risk approaches for Mujika area; To establish the current status of climatic risk information and dissemination practices in Mujika area; To document the social/institutional aspects that enable farmers to adopt appropriate alternative interventions; and To operationalise the community agrometeorological participatory extension service (CAPES) so as to evaluate its effectiveness. Data collection used both quantitative and qualitative methods. The quantitative approach analyzed long-term rainfall data while the qualitative approach used Participatory Rural Appraisal (PRA). Community members from three villages (Nkabika, Bulimo and Malomo) participated in PRA exercises by presenting spatial data (in community sketch maps, farm sketches and transect walks), time related information (by historical time and trend lines) and social data (from household interviews, daily calendar according to gender and institutional analysis) throughout the study. They organized their problems and opportunities into a priority order at the village level, resulting in the creation of a community information dissemination plan (CIDP). The implementation of the CIDP included weekly local radio broadcasts of specially prepared programmes which were then recorded by local club representatives. The farmers organized themselves into five small radio listening clubs where they listened and discussed the re-recorded programmes. Their learning by doing was around the mother field trial managed by the other PhD student, Prospard Gondwe and baby field trials conducted by 16 local farmer volunteers in their own fields. Monitoring and evaluation was incorporated into the project by these volunteer farmers keeping records of most project activities. A community agrometeorological participatory extension service (CAPES) developed out of these interactions between stakeholders, including community members, agriculture extension officers, an agrometeorologist and agronomist during all these activities. CAPES is an agrometeorogical extension service including monitoring, developed together with a community to give tailor-made climatic information for improved agricultural decision making. Stories of five selected Mujika farmers were used to evaluate the effectiveness of CAPES in disseminating climatic information to smallholder farmers in Mujika. This assisted understanding the influence of CAPES on individuals across a range of different types of farmers that are present in Mujika, according to status, education and influence of authority. The study findings led to the following conclusions: Although long-term rainfall data analysis was useful in understanding smallholder farmers‟ environment, it was also instrumental in characterising available annual and seasonal rainfall trends. Detailed intra-seasonal information (start and end of rain, dry spell length) used together with seasonal forecasts helped improve agricultural decision making. Indigenous forecast knowledge plays a major role in smallholder farmers‟ agricultural decision making and planning of crop management options for every unfolding season when access to seasonal climate forecast information is limited. The fact that the community had a good knowledge of the natural resources enabled them to recognize that the use of climate information was a viable opportunity to improve crop productivity. The lack of credibility of researchers and Zambia Meteorological Department (ZMD) within the community to produce and disseminate seasonal climate forecasts had a negative influence on farmers‟ acceptance and usage of seasonal climate forecasts. A sustainable community agrometeorological participatory extension strategy depends on smallholder farmers‟ contributions during planning as users because farmers know what climatic information is required for addressing their problems and the best dissemination modes for effective information utilization. It is possible to develop an effective and appropriate community agrometeorological participatory extension service with a community when appropriate participatory approaches to community interactions are used. The stories of the identified farmers used in the qualitative approach provided the visible evidence of the influence of the CAPES on the farming systems in Mujika. All this information was combined into a practical handbook on CAPES to be used to train agrometeorological intermediaries. Recommendations that follow from this thesis and that may also help as starting points for future research are: Participatory dissemination of climatic information should be based on a well-researched community baseline so as to address actual community problems. The participatory multi-disciplinary climatic information dissemination plan should be develop together with farmers and other stakeholders for an effective information flow in the community. In order to improve smallholder farmers‟ agricultural decision making and crop management options in rainfed systems, an effective dissemination of seasonal climate forecast and a detailed long-term rainfall analysis for their respective area is required. The community agrometeorological extension strategy (CAPES) developed during the dissemination of climatic information to smallholder farmers in Mujika area is a model of success and is recommended for application to other areas. Use of stories about selected farmers in evaluating the effectiveness of community interactions is a useful approach and is recommended. The CAPES handbook, developed during this project, is a useful guide and is recommended for use by anyone intending to interact with communities for the dissemination of climatic risk information. The community agrometeorological participatory extension strategy should be evaluated in future in five or ten years after it establishment.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2010
Keywords: Climatic changes -- Risk assessment; Meteorology, Agricultural -- Zambia -- Information services; Weather forecasting; Crops and Climate